2022
DOI: 10.1111/psyp.14030
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in expectation‐based novel word learning

Abstract: Adult language users can infer the meaning of a previously unfamiliar word from a single exposure to this word in a semantically and thematically constrained context, henceforth, predictive context (Borovsky et al., 2010 Cognition, 116(2), 289–296; Borovsky et al., 2012 Language Learning and Development, 8(3), 278–302). Children use predictive contexts to anticipate upcoming stimuli (Borovsky et al., 2012 Language Learning and Development, 8(3), 278–302; Mani & Huettig, 2012 Journal of Experimental Psychology:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…and surprising or rare events can induce better learning (e.g., Brod, Hasselhorn & Bunge, 2018;Vergilova et al, 2022). These explanations are consistent with the long-held idea that invariance detection is enhanced amid variation (Gibson, 1969;Gogate & Hollich, 2010).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…and surprising or rare events can induce better learning (e.g., Brod, Hasselhorn & Bunge, 2018;Vergilova et al, 2022). These explanations are consistent with the long-held idea that invariance detection is enhanced amid variation (Gibson, 1969;Gogate & Hollich, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Further, it is important to note that rarity and/or surprise can make structures more noticeable and learnable, so if word‐touch alignment is relatively rare as compared to speech‐alone input, then occurrences of word‐touch could be particularly helpful to the young infant learner given their ability to garner attention and aid in learning. Specifically, unexpected or rare stimuli show clear differences in brain responses (e.g., the P3 in oddball tasks; Squires et al., 1975; Sakamoto & Love, 2006); and surprising or rare events can induce better learning (e.g., Brod et al., 2018; Vergilova et al., 2022). These explanations are consistent with the long‐held idea that invariance detection is enhanced amid variation (Gibson, 1969; Gogate & Hollich, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other research investigating neural signatures of word learning from context in school-aged children found that age modulated how sentence constraint influenced the neural response to unfamiliar words in context, as well as how those same novel words could be used as semantic primes after an initial learning procedure ( Vergilova et al, 2022 ). More specifically, children under 10 showed sensitivity to measures of constraint, as measured by N400 responses to pseudowords embedded within sentence contexts, but showed relatively weak semantic priming effects when those words were later used as primes for known, real words.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, even in good readers aged 10–11 years the functional lateralization of linguistic neural networks involved in automatic word recognition and phonological processing is still not developed 49 , 50 . Although neurophysiological evidence suggests that early adolescents use similar strategies to adults in processing and learning new words and can effectively use context to anticipate incoming information 51 , 52 , the visual word processing system continues to develop 53 .…”
Section: Introductionmentioning
confidence: 99%